CODE-SWITCHING AS GLOBAL YOUTH DISCOURSE: A QUALITATIVE STUDY OF INDONESIAN-ENGLISH MIXING IN INDONESIAN POP SONGS (2020-2025) - Ria Yuliasari; Rika Virtianti; Ferdias Prihatna Sari (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the use of Indonesian–English code-switching in Indonesian pop song lyrics released between 2020 and 2025. The research aims to identify the types of code-switching used in the selected songs and to explore how such linguistic practices reflect global youth discourse in contemporary popular music. This study employs a qualitative descriptive method with a sociolinguistic approach. The primary data consist of song lyrics from five Indonesian pop songs: Lathi by Weird Genius (2020), Asmarandhana by Kamar Jiwa (2022), It’s Only Me by Kaleb J (2022), Garam dan Madu by Tenxi, Naykilla, and Jemsii (2024), and Alamak by Rizki Febian and Adrian Khalif (2025). The analysis applies the theory of types of code-switching, which includes inter-sentential switching, intra-sentential switching, and tag switching. The results show that a total of 52 instances of code-switching were identified in the data. Inter-sentential switching is the most dominant type with 36 occurrences, followed by intra-sentential switching with 15 occurrences, while tag switching appears only once. These findings indicate that code-switching in Indonesian pop song lyrics is frequently used as a stylistic and expressive strategy to emphasize emotional meaning and lyrical creativity. Furthermore, the use of Indonesian–English mixing reflects the influence of globalization and digital culture on contemporary youth communication. In conclusion, code-switching in Indonesian pop music functions not only as a linguistic phenomenon but also as a representation of global youth discourse that connects local identity with global cultural trends.